Assessing the Impact of Community-Based Oral Health Education and Preventive Programs on Awareness and Treatment Compliance in Underserved Populations - Rehana Kausar, Shamima Abdullah, Abid Ali Ranjha, Adnan Sukkarwalla, Saleem Adil, Muhammad Sami Iqbal (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Underserved populations face substantial barriers to oral health awareness and treatmentadherence. This experimental study evaluates the effectiveness of community-based oral healtheducation and preventive programs on improving awareness and treatment compliance